PEMETAAN TEMA DAN POLA PENULISAN MANUSKRIP HADIS DI INDONESIA - Ismail Yahya; Farkhan Farkhan (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Although Hadith is one of the main sources of Islamic teachings but the science of Hadith has received less attention from scholars who concern on Islamic studies in Islamic Higher Education Institutions (PTKI) in Indonesia. This can be seen from the lack of research on Hadith manuscripts. This study is intended to fill the gap and aims at mapping the theme and pattern of writing of Hadith manuscripts founded in the collection of the National Library of Republic of Indonesia. Of the 32 Hadith manuscripts, only 11 have been studied. The method used refers to the codicology and theory of ilmu Fahrah al-Ḥadīṡ. The findings of this study are that 1) it is assumed, from the theme mapping, that those Hadith manuscripts are summaries of the main Hadith books, whose content is related to the problem of the occult, the Prophet’s moral (akhlaq), virtues of deeds (fadhilat al-a’mal), encouragement of good (targhib) and discouragement of evil (tarhib). Another finding is 2) in terms of the writing pattern of Hadith, based on the knowledge of Fahrah al-Ḥadīṡ, there are 8 patterns of writing of the Hadith based on Hadith manuscripts examined, namely the writing pattern of al-Muʻjam, Arbaʻīnāt, Taʻāliq, Ṡulāsiyyāt, Takhrīj, al-Mukhtaṣarāt, Syaraḥ Ḥadīṡ, and Ḥadīṡ Masyḥūr.